A Survey of Essential Genome Stability Genes Reveals That Replication Stress Mitigation Is Critical for Peri-Implantation Embryogenesis - Kafer, Georgia R.; Cesare, Anthony J. (Frontiers in Cell and Developmental Biology, 2020)
Murine development demands that pluripotent epiblast stem cells in the peri-implantation embryo increase from approximately 120 to 14,000 cells between embryonic days (E) 4.5 and E7.5. This is possible because epiblast stem cells can complete cell cycles in under three hours in vivo. To ensure conceptus fitness, epiblast cells must undertake this proliferative feat while maintaining genome integrity. How epiblast cells maintain genome health under such an immense proliferation demand remains unclear. To illuminate the contribution of genome stability pathways to early mammalian development we systematically reviewed knockout mouse data from 347 DDR and repair associated genes. Cumulatively, the data indicate that while many DNA repair functions are dispensable in embryogenesis, genes encoding replication stress response and homology directed repair factors are essential specifically during the peri-implantation stage of early development. We discuss the significance of these findings in the context of the unique proliferative demands placed on pluripotent epiblast stem cells.